PRIVATE EQUITY MARKET IN THE ECOSYSTEM OF START-UPS AND SME SECTOR – PART 1 - Waściński, Tadeusz; Dudkowska, Anna; Kurovs, Jevgenijs (Management and Administration Journal, 2020)
Private Equity (PE)/Venture Capital (VE) Funds cover medium and long-term transactions on the private enterprise market. They adopt a legal form of closed-ended investment funds or more and more appreciated alternative investment companies, which contribute to a development of innovativeness in the Polish economy, supporting enterprises on each level of their expansion. Over the last years, there has been an increased value of investment reported among the European PE funds. Poland’s share in the Central and Eastern European (CEE) investments has been the highest in the region and does not fall below 46%. Moreover, more than a double increase of domestic PE investments in 2017 is an opportunity for improving one of the lowest innovation indexes in the European Union. An important role in this matter also belongs to the growing power of start-up ecosystem. It is not without significance that there is a growing awareness of start-ups cooperating with funds, which is defined e.g. by a stronger position of investor or a limited possibility to negotiate the terms of investment agreements. The aim of this article is to present the PE market and its meaning in the development of young companies. Showing in the first part of the article statistics related to management of venture capital in Poland compared to Europe and the CEE will identify tendencies in development of the Polish PE market. It will also allow estimating Poland’s chances for improving its position in the innovative European ranking and increasing Poland’s competitiveness on the international level. Emphasising the importance of startup’s education in dealing with VC funds in the second part of the study will additionally highlight the essence of their cooperation in terms of professionalization of the PE market and a growth of the country’s innovativeness.